Workflow integration analysis of a human factors-based clinical decision support in the emergency department. (November 2021) - Salwei, Megan E.; Carayon, Pascale; Hoonakker, Peter L.T.; Hundt, Ann Schoofs; Wiegmann, Douglas; Pulia, Michael; Patterson, Brian W.
Abstract: Numerous challenges with the implementation, acceptance, and use of health IT are related to poor usability and a lack of integration of the technologies into clinical workflow, and have, therefore, limited the potential of these technologies to improve patient safety. We propose a definition and conceptual model of health IT workflow integration. Using interviews of 12 emergency department (ED) physicians, we identify 134 excerpts of barriers and facilitators to workflow integration of a human factors (HF)-based clinical decision support (CDS) implemented in the ED. Using data on these 134 barriers and facilitators, we distinguish 25 components of workflow integration of the CDS, which are described according to four dimensions of workflow integration: time, flow, scope of patient journey, and level. The proposed definition and conceptual model of workflow integration can be used to inform health IT design; this is the purpose of the proposed checklist that can help to ensure consideration of workflow integration during the development of health IT. Highlights: We propose a definition and conceptual model of workflow integration of health IT. We identify barriers and facilitators to workflow integration of a CDS in the ED. We describe 25 components of workflow integration of a CDS. We propose a checklist to help consider workflow integration in health IT design.